Professional Reasoning in Occupational Therapy: A Scoping Review - Luis-Javier M; José-Ignacio; Miguel-Ángel Ta; Pedro Moruno-Millares (Hindawi-Wiley, 2019)
Background/Aim. Professional reasoning in occupational therapy is the process used by practitioners to plan, direct, perform, and reflect on client care. The professional's ability to manage the process of the intervention is structured around it, thereby influencing the effectiveness of the work carried out. The objectives of this research were to identify and describe (a) the historical development of this area of research from 1982 to 2017 and (b) the nature and volume of the scientific literature on professional reasoning in occupational therapy and the evidence that exists today. Methods. A scoping review method was used to carry out an historical mapping of research on professional reasoning and to summarise the lines of research explored to date. The review was conducted in five stages following the PRISMA guidelines. After applying the selection criteria, the search identified 303 references. Results. The results are presented under three headings: (a) nature and volume of publications on professional reasoning in occupational therapy according to number and year of publications, journal, country, author, and line of research; (b) historical trends in the scientific literature on professional reasoning in occupational therapy since 1982; and (c) methodological aspects of the research. Each of them is discussed through statistical analysis. Conclusions. The research about professional reasoning in occupational therapy is a field of empirical nature, in which qualitative studies predominate. Principal lines of research are focused on specific fields of practice, undergraduates, and theoretical aspects of professional reasoning. There were identified three historical phases with common features in terms of objectives and research methods.